2005
DOI: 10.1159/000088667
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of the Posterior Inferior Cerebellar Artery Territory Infarcts

Abstract: Background and Purpose: The clinical, etiological and stroke mechanisms are defined well before but the detailed clinical and etiologic mechanisms regarding to all clinical spectrum of posterior inferior cerebellar artery (PICA) infarcts were not systematically studied by diffusion-weighted imaging (DWI). Methods: Seventy-four patients with PICA territory ischemic lesion proved by DWI with decreased apparent diffusion coefficient and FLAIR (fluid attenuation inversion recovery) included in our Registry, corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 47 publications
1
34
0
1
Order By: Relevance
“…It is well known that territorial cerebellar infarcts are frequently associated with cardioembolism or artery-to-artery embolism [1,2,3,4,5,6, 9, 20]. However, small cerebellar infarction has rarely been investigated until recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that territorial cerebellar infarcts are frequently associated with cardioembolism or artery-to-artery embolism [1,2,3,4,5,6, 9, 20]. However, small cerebellar infarction has rarely been investigated until recently.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that embolism from an arterial or cardiac source is the most common cause of territorial cerebellar infarcts [1,2,3,4,5,6,7]. Previous studies showed that small nonterritorial cerebellar infarcts usually have the same embolic mechanism as territorial infarcts, and they sometimes have a hemodynamic mechanism [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed dysarthria in a patient with concomitant AICA and PICA lesions. Dysarthria was reported in different frequencies in individuals with infarcts in the AICA and PICA territories [43,44,45,46,47]. These differences may be due to the retrospective study design, different frequencies of brainstem involvement and the absence of a standardized evaluation of dysarthria.…”
Section: Discussionmentioning
confidence: 99%
“…In the ischemic cases, the prognosis of PICA infarction is generally good [18, 19] except for patients with multiple brainstem lesions [20]; in the SAH cases, the prognosis of vertebrobasilar dissections is usually poor with regard to the initial state, and there is a high risk of rebleeding [21, 22]. Dissecting aneurysm of the PICA carries a 24% risk of rebleeding in the acute phase, associated with a high mortality rate [23].…”
Section: Discussionmentioning
confidence: 99%